An Extenics-TRIZ integrated RFPS model for different object of design requirements. - Fangzhi Gui; Jing Zhou; Xiangdong Sun; Jianfei Lu; Sheng Cao (PLoS ONE)
Extending product life is one of the effective ways to reduce the waste of resources. However, many unsatisfactory products are scrapped because of a lack of adequate performance. The product should be improved and upgraded innovatively, and the existing upgradable products may create more economic benefits for the longer product life cycles. This paper proposed a product innovative design and product upgrade employing an Extenics-TRIZ Integrated requirement-function-principle-structure (RFPS) model, which aims at complex requirement flexibility with easy-to-use design process when the product needs a redesign. Here, the requirement flexibility refers to the ability of a design object to adapt its design levels. There are two design strategies: the extension analysis methods are utilized to map the top-level requirements to functions, principles, and structures requirements, and then the TRIZ is used to handle the design problems according to the objects on different levels. This design knowledge is summarized as RFPS, and it can be reused in computer-aided innovation further. A case study for a cutting table is illustrated to the innovation and upgrade, and it indicates the effectiveness for designers to implement the design methodology.